Molecular analysis of single circulating tumour cells following long‐term storage of clinical samples. Issue 12 (24th October 2017) - Mesquita, Barbara; Rothwell, Dominic G.; Burt, Deborah J; Chemi, Francesca; Fernandez‐Gutierrez, Fabiola; Slane‐Tan, Daniel; Antonello, Jenny; Carter, Mathew; Carter, Louise; Parry, Marina; Franklin, Lynsey; Marais, Richard; et al.
Abstract : The CellSearch ® semiautomated CTC enrichment and staining system has been established as the 'gold standard' for CTC enumeration with CellSearch ® CTC counts recognized by the FDA as prognostic for a number of cancers. We and others have gone on to show that molecular analysis of CellSearch ® CTCs isolated shortly after CellSearch ® enrichment provides another valuable layer of information that has potential clinical utility including predicting response to treatment. Although CellSearch ® CTCs can be readily isolated after enrichment, the process of analysing a single CellSearch ® patient sample, which may contain many CTCs, is both time‐consuming and costly. Here, we describe a simple process that will allow storage of all CellSearch ® ‐enriched cells in glycerol at −20 °C for up to 2 years without any measurable loss in the ability to retrieve single cells or in the genome integrity of the isolated cells. To establish the suitability of long‐term glycerol storage for single‐cell molecular analysis, we isolated individual CellSearch ® ‐enriched cells by DEPArray™ either shortly after CellSearch ® enrichment or following storage of matched enriched cells in glycerol at −20 °C. All isolated cells were subjected to whole‐genome amplification (WGA), and the efficacy of single‐cell WGA was evaluated by multiplex PCR to generate a Genome Integrity Index (GII). The GII results from 409 single cells obtained from both 'spike‐in' controls and clinical samples showed no statistical difference between values obtained pre‐ and postglycerol storage and that there is no further loss in integrity when DEPArray™‐isolated cells are then stored at −80 °C for up to 2 years. In summary, we have established simple yet effective 'stop‐off' points along the CTC workflow enabling CTC banking and facilitating selection of suitable samples for intensive analysis once patient outcomes are known. Abstract : Here, we describe a simple process for the storage of CellSearch ® ‐enriched cells for up to 2 years without any measurable loss in the ability to retrieve single cells, or in the genome integrity of the isolated cells. This workflow enables CTC banking and facilitates the retrospective selection of samples for intensive analysis once patient outcomes are known.